A case study on the Political Dynasty of San Miguel, Leyte since 1987 up to the present - Costa, Christine Joyce; Villanueva, Paul Thomas (Tacloban City Christine Joyce Costa [and] Paul Thomas Villanueva, 2011)
The study focuses on the presence of political dynasty in San Miguel, Leyte from 1987 since the prohibition of Political Dynasty indicated in the crafting of 1987 Constitution. The objectives of the study are to identify political families that fall on the definition of political dynasty that there is succession in the family in holding prominent political roles in the community and families and relatives that occupy public offices, to characterize the identified families, factors that made them last in politics as well as their downfall, their resurgence in politics, and the points of key informants on the presence of political dynasty in the municipality.
Key informants serve as respondents for the study as well as the incumbent officials that truly know the identified families. The authors used an interview questionnaire to gather all those necessary information to answer the objectives.
The results revealed that based on the available records, the Lapidario and Brazil family dominated the politics in San Miguel, Leyte in terms of numbers and length of time that the family member holds position. Respondents characterize these families to be "Makitawo" (People oriented), "Mag-upay" (Good), "Nakakabulig" (Helpful) and "Pulitiko" (Politicians). The political families believe that they were successful in serving the municipality for long because of their good performance and service rendered to their constituents and the love of the people for them. The Key informants also believe that these families have sufficient resources such as money, land, vehicles and machines which includes the people and wards that were helpful in continuing their own legacy. In addition, party affiliation and family support were considered by the candidates as factors for their victory.
Despite holding several positions, both families experienced defeat due to lack of sufficient support for the people and party, as well as popularity. Their age was also a factor for their misfortune in aspiring for higher position. However, even though they were defeated most of them tried their luck in the following elections and earned a sufficient support and experience to be able to return to power. Some key informants believe that political dynasty can be good and sometimes bad for the municipality. However some of them were vocal that political dynasty is not good for the municipality and some appreciate the presence of the dominant families. In terms of supporting possible challengers of the dominant families, some key informants were undecided in supporting the contender since they were not yet certain of who will challenge and what their personal backgrounds are. However, some were decided to try new leadership and reinstate these families once their contenders were incompetent in the position. But some were devoted loyalists who are keen enough to still vote for their admired political families for these families are deserving enough of their support.
The findings of this study are important because they can shed light in to the presence of political dynasty in the municipality.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban.
Keywords: Social Science